FIRST EXPERIENCE OF PLASTIC CLOSING OF A SKULL DEFECT BY POLYTETRAFLUOROETHYLENE-BASED COMPOSITE MATERIAL IN AN EXPERIMENT - Dovnar A. I.; Dovnar R. I. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2020)
Background. Despite the presence of a great number of repair methods for skull defects, the ideal material that allows the doctor to optimally restore the integrity of the skull has not yet been found. In this regard, it becomes advisable to use composite materials in plastic neurosurgery. Aim of the research. To substantiate experimentally the possibility of using the composite material “Superfluvis” for cranioplasty and to compare it with the titanium plate used for the same purpose. Material and methods. Laboratory rabbits were subjected to experimental craniotomy with its plastic closure by titanium (the control group) and the “Superfluvis” material (the experience group). We studied the neurological state of the animals, the biochemical blood analysis, and tissues around the location of plastic materials. Results. The obtained data demonstrated the absence of negative influence of the material “Superfluvis” on the indices of biochemical blood analysis, histological state of the tissues surrounding the transplant, and animal neurological status. Conclusions. The composite material "Superfluvis" turned out to be an effective plastic material for closing defects of the skull in the experiment. In perspective, it can be used for cranioplasty in humans after conducting a series of additional studies.